2018
DOI: 10.1038/s41563-018-0099-0
|View full text |Cite
|
Sign up to set email alerts
|

Local immunomodulation with Fas ligand-engineered biomaterials achieves allogeneic islet graft acceptance

Abstract: Islet transplantation is a promising therapy for type 1 diabetes. However, chronic immunosuppression to control rejection of allogeneic islets induces morbidities and impairs islet function. T-effector cells are responsible for islet allograft rejection and express Fas death receptor following activation, becoming sensitive to Fas-mediated apoptosis. Here, we report that localized immunomodulation using microgels presenting an apoptotic form of Fas ligand (SA-FasL) results in prolonged survival of allogeneic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 44 publications
(48 reference statements)
11
114
0
Order By: Relevance
“…In this study, we sought to circumvent the toxicity of systemic immunotherapy delivery by implementing previously described synthetic microgels for the immobilization and targeted local delivery of PD-L1. This microgel platform has previously been used for controlled surface protein presentation of FasL (19). While FasL is a potent homeostatic mediator of activation-induced cell death (33), its potential therapeutic translation may be limited by the broad effects of FasL as an immunomodulator of inflammation (34) and, possibly, activation of innate immune responses (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we sought to circumvent the toxicity of systemic immunotherapy delivery by implementing previously described synthetic microgels for the immobilization and targeted local delivery of PD-L1. This microgel platform has previously been used for controlled surface protein presentation of FasL (19). While FasL is a potent homeostatic mediator of activation-induced cell death (33), its potential therapeutic translation may be limited by the broad effects of FasL as an immunomodulator of inflammation (34) and, possibly, activation of innate immune responses (35).…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge in protein delivery is the relatively short half-life encountered in vivo, leading to unreliable efficacy or the requirement of frequent dosing, which exacerbates costs and can have clinically undesirable outcomes. We previously showed that immunomodulatory protein delivery via microgels improves retention of SA-FasL, an apoptotic modulator, in the kidney capsule (19). Although the biomaterial platform is similar, various features of the SA-PD-L1 protein, such as the sequence, molecular weight, and three-dimensional structure, are different from SA-FasL, which can affect its bioavailability and turnover kinetics.…”
Section: Microgels Enhance Sa-pd-l1 Retention In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fas cell surface death receptor (Fas), which belongs to the tumor necrosis factor receptor super family, is a trans-membrane protein that is widely expressed on the cytoplasmic membrane. After interacting with its ligand, Fas can promote the apoptotic signal in cells ( 46 , 50 ). MTE was able to enhance the curative effect of doxorubicin chemotherapy in MG63 osteosarcoma cells, through upregulation of Fas expression in tumor cells ( 30 ).…”
Section: Marsdenia Tenacissima Effects Against Other Tumorsmentioning
confidence: 99%
“…Alternatively, islets grafts have been engineered with immunoregulatory biologics to achieve long-term graft survival without the use of chronic immunosuppression. Thus changing the ratio of T-effector vs. T-regulatory cells (83) or creating local immunomodulation using modified microgels exhibiting Fas ligand improves long-term survival of allogenic islets grafts in diabetic mice (23). In addition to being hypoimmunogenic, hESC-derived PPs have a lower oxygen requirement compared with ␤-like cells, which could allow better survival upon transplantation before graft vascularization by the host occurs (49,50).…”
Section: Engraftmentmentioning
confidence: 99%